2016
DOI: 10.1073/pnas.1612094113
|View full text |Cite
|
Sign up to set email alerts
|

System crash as dynamics of complex networks

Abstract: Complex systems, from animal herds to human nations, sometimes crash drastically. Although the growth and evolution of systems have been extensively studied, our understanding of how systems crash is still limited. It remains rather puzzling why some systems, appearing to be doomed to fail, manage to survive for a long time whereas some other systems, which seem to be too big or too strong to fail, crash rapidly. In this contribution, we propose a network-based system dynamics model, where individual actions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 38 publications
(36 reference statements)
3
37
0
Order By: Relevance
“…This contrasts with the initial assumption of resilience models for online social networks (Garcia et al, ): a monotonically decreasing inactivity probability with degree. Our results show that a general negative trend is in place, but also show a concavity pattern that calls for new microdynamic formulations, as suggested in the framework of Garcia et al () and recently explored by Yu et al (). Nevertheless, we must note that the cascading inactivity hypothesis follows from these kind of models, which we find support for when comparing the quality of predictors based on degree and coreness.…”
Section: Discussionsupporting
confidence: 80%
“…This contrasts with the initial assumption of resilience models for online social networks (Garcia et al, ): a monotonically decreasing inactivity probability with degree. Our results show that a general negative trend is in place, but also show a concavity pattern that calls for new microdynamic formulations, as suggested in the framework of Garcia et al () and recently explored by Yu et al (). Nevertheless, we must note that the cascading inactivity hypothesis follows from these kind of models, which we find support for when comparing the quality of predictors based on degree and coreness.…”
Section: Discussionsupporting
confidence: 80%
“…8 Furthermore, it has been demonstrated that lncRNA regulate genes in cis and their transcription per se , not the actual sequence, is activating the adjacent gene. 9 Considering that there are many such lncRNA/protein coding RNA gene pairs in our genome, 10 it is important to determine the extent and functions of protein coding gene regulation by adjacent lncRNA genes.…”
mentioning
confidence: 99%
“…Perturbing a node to influence one layer inadvertently affects the other layers that the node is active in, which can have drastic unintended consequences [5,[16][17][18]. Therefore, it is desirable to identify targets in a multiplex network that maximize our influence in certain layers, yet minimize any unwanted impact on others.…”
Section: Introductionmentioning
confidence: 99%